Respuesta :
Answer:
option A
f(x) = (x – 1)2 + 3
Step-by-step explanation:
Given in the question a function,
f(x) = 4 + x² – 2x
Step 1
f(x) = 4 + x² – 2x
here a = 1
b = -2
c = 4
Step 2
x = -b/2a
h = -(-2)/2(1)
h = 2/2
h = 1
Step 3
Find k
k = 4 + 1² – 2(1)
k = 3
Step 4
To convert a quadratic from y = ax² + bx + c form to vertex form,
y = a(x - h)²+ k
y = 1(x - 1)² + 3
y = (x - 1)² + 3
ANSWER
The vertex form is
[tex]f(x) = {(x - 1)}^{2} + 3[/tex]
EXPLANATION
The given function is
[tex]f(x) = 4 + {x}^{2} - 2x[/tex]
This is the same as:
[tex]f(x) = {x}^{2} - 2x + 4[/tex]
We add and subtract the square of half the coefficient of x.
[tex]f(x) = {x}^{2} - 2x + {( -1 )}^{2} - {( -1 )}^{2} + 4[/tex]
[tex]f(x) = {x}^{2} - 2x + 1 - 1 + 4[/tex]
The first three term is a perfect square trinomial:
[tex]f(x) = {(x - 1)}^{2} + 3[/tex]
The vertex form is
[tex]f(x) = {(x - 1)}^{2} + 3[/tex]